Screening for the optimal induction parameters for periplasmic producing interferon-α2b in Escherichia coli - Azaman, Siti Nor Ani; Ramakrishnan, Nagasundara Ramanan; Tan, Joo Shun; Abdul Rahim, Raha; Abdullah, Mohd Puad; Ariff, Arbakariya (Academic Journals, 2010)
Screening for optimum induction parameters to improve the production of periplasmic interferon-α2b (PrIFN-α2b) by recombinant Escherichia coli was conducted using shake flask culture. Recombinant E. coli Rosetta-gami 2(DE3) harboring the plasmid pET26b containing IFN-α2b gene under the control of the T7lac promoter was used, where the induction was accomplished by isopropyl β-D-1-thiogalactopyranoside (IPTG). The induction parameters (inducer concentration, point of induction, induction temperature and the length of induction) were analyzed to find the suitable range to be used for further optimization process. From the analysis, narrow range of induction temperature from 16 to 30°C and IPTG lower than 2 mM were found suitable for induction of PrIFN-α2b. On the other hand, early log phase was the preferred time to initiate the induction and the length of induction was dependent on the combination of other induction parameters used.